Assessing heavy metal contamination in Sado Estuary - Caeiro, Sandra (2011)
The Sado Estuary in Portugal is a good example of a site where human pressures and ecological values collide with each other. An overall contamination assessment has never been conducted in a way that is comprehensible to estuary managers. One of the aims of this work was to select different types of index to aggregate and assess heavy metal contamination in the Sado Estuary in an accessible manner. Another aim was to use interpolation surfaces per metal to compare and gauge the results of the indices and to assess the contamination separately per metal. Seventy-eight stations were sampled within the main bay of the estuary and a set of heavy metals and metalloids was established, Cd, Cu, Pb, Cr, Hg, Al, Zn and As. The sediment fine fraction content, organic matter and redox potential were also analysed. Various indices for contamination, background enrichment and ecological risk were used, tested, compared and performance-evaluated. All metals and metalloids were strongly correlated, and the indices appear to reflect heavy metal variability satisfactorily. Difficulties were found in some indices regarding boundary definition (minimum and maximum) and comparability with other estuaries, thus better methods of standardization should be a priority issue. According to the index that has the highest performance score within the group of ecological risk indices – the Sediment Quality Guideline Quotient – only 3% of the stations are highly contaminated and register a high potential for observing adverse biological effects, whereas 47% display moderate contamination. This index can be complemented with the contamination index, which allows more site-specific and accurate information on contaminant levels. If the aim of work on contamination evaluation is to assess the overall contamination of a study area, the indices are highly appropriate. For spatial and source evaluation per metal, interpolation surfaces should also be used.